Design, synthesis, crystal structure and luminescent properties introduced by Eu3+ of a new type of rare-earth borophosphate CsNa2REE2(BO3)(PO4)2 (REE = Y, Gd). Issue 29 (14th July 2020) - Zhao, Dan; Xue, Yali; Zhang, Ruijuan; Fan, Yanping; Liu, Baozhong; Li, Yanan; Zhang, Shirui
Abstract : This work provides a novel host lattice template CsNa2 REE2 (BO3 )(PO4 )2 (REE = Y, Gd, Lu) for Eu 3+ luminescence, with a linear arrangement of REE 3+ ions that restricts the occurrence of concentration quenching even for fully concentrated Eu 3+ . Abstract : The rich compositional and structural diversity of borophosphates provides a wide variety of host lattices for luminescent materials. Herein, we report a borophosphate, CsNa2 REE2 (BO3 )(PO4 )2 (REE = Y, Gd), with a new type of three-dimensional (3D) anionic framework of [REE2 (BO3 )(PO4 )2 ]∞ . In this structure, REE 3+ ions are in a linear array and the nearest intraline REE–REE distance is above 6.9 Å. Surprisingly, the Eu 3+ activated phosphors CsNa2 REE2(1− x ) Eu2 x (BO3 )(PO4 )2 show an insignificant concentration quenching effect; the higher the Eu 3+ concentration, the larger the absolute luminescent external quantum yield. The 100% Eu 3+ phosphor CsNa2 Eu2 (BO3 )(PO4 )2 possesses an IQY of 59% under 394 nm excitation. Moreover, CsNa2 Eu2 (BO3 )(PO4 )2 phosphor possesses superior thermal stability in the range 30–200 °C, retaining more than 96% of its initial intensity at 200 °C. We believe the prepared phosphor has potential application as a red phosphor for NUV excited LEDs.